Copper as a Robust and Transparent Electrocatalyst for Water Oxidation1. (7th January 2015) - Du, Jialei; Chen, Zuofeng; Ye, Shengrong; Wiley, Benjamin J.; Meyer, Thomas J.
Abstract Copper metal is in theory a viable oxidative electrocatalyst based on surface oxidation to CuIII and/or CuIV, but its use in water oxidation has been impeded by anodic corrosion. The in situ formation of an efficient interfacial oxygen‐evolving Cu catalyst from CuII in concentrated carbonate solutions is presented. The catalyst necessitates use of dissolved CuII and accesses the higher oxidation states prior to decompostion to form an active surface film, which is limited by solution conditions. This observation and restriction led to the exploration of ways to use surface‐protected Cu metal as a robust electrocatalyst for water oxidation. Formation of a compact film of CuO on Cu surface prevents anodic corrosion and results in sustained catalytic water oxidation. The Cu/CuO surface stabilization was also applied to Cu nanowire films, which are transparent and flexible electrocatalysts for water oxidation and are an attractive alternative to ITO‐supported catalysts for photoelectrochemical applications.